Tuning redox chemistry and photophysics in core-substituted tetraazaperopyrenes (TAPPs) - Geib, Sonja; Martens-Kruck, Susanne; Märken, Michaela; Rybina, Arina; Wadepohl, Hubert; Gade, Lutz H. (Chemistry - a European journal, 2013)
Core substitution of tetraazaperopyrenes (TAPPs) has been achieved, and with it, considerable variation of their photo- and redox-chemical properties. Through Suzuki cross coupling starting from the fourfold core-brominated tetraazaperopyrene, aryl-substituted TAPPs were synthesized, which displayed very high fluorescence quantum yields (up to 100 %) in solution. Besides the Suzuki reactions, Stille and Sonogashira cross-couplings were also found to be suitable methods for core derivatization, as demonstrated in the syntheses of alkynyl-substituted tetraazaperopyrene congeners. Furthermore, TAPPs incorporating intramolecular donor-acceptor combinations of aromatic units (8, 9) were accessible by coupling the electron-poor peropyrene core with electron-rich aromatic units, which act as strong electron donors. Finally, C-heteroatom coupling (O, S, N) gave rise to novel TAPP derivatives with strongly modified redox-chemical behaviour and photophysics in the solid state as well in solution. In particular, TAPP derivatives displaying red fluorescence were obtained for the first time.
Gesehen am 29.01.2020